Dysregulated Glucose Metabolism as a Therapeutic Target to Reduce Post-traumatic Epilepsy - Koenig, Jenny B.; Dulla, Chris G. (Frontiers in Cellular Neuroscience, 2018)
Traumatic brain injury is a significant cause of disability worldwide and can lead to post-traumatic epilepsy. Multiple molecular, cellular, and network pathologies occur following injury which may contribute to epileptogenesis. Efforts to identify mechanisms of disease progression and biomarkers which predict clinical outcomes have focused heavily on metabolic changes. Advances in imaging approaches, combined with well-established biochemical methodologies, have revealed a complex landscape of metabolic changes that occur acutely after traumatic brain injury, and then evolve in the days to weeks after. Based on this rich clinical and preclinical data, combined with the success of metabolic therapies like the ketogenic diet in treating epilepsy, interest has grown in determining whether manipulating metabolic activity following traumatic brain injury may have therapeutic value to prevent post-traumatic epileptogenesis. Here, we focus on changes in glucose utilization and glycolytic activity in the brain following traumatic brain injury and during seizures. We review relevant literature and outline potential paths forward to utilize glycolytic inhibitors as a disease-modifying therapy for post-traumatic epilepsy.